Hong Kong entrepreneurs : a comparison with Singapore entrepreneurs - Lo, Selina Pin Huen (2015)
The role of entrepreneurship in economic development is well recognized. There are three characteristics of entrepreneurs. He is first, a risk taker, willing to take calculated risk; second an organiser with the ability to plan, control and coordinate the various factors of production to maximum efficiency; and lastly, an opportunist who is ever ready to pounce on any chance. There are extensive discussion in the literature on whether the umque characteristics of entrepreneur are determined by nature or nurture only confirms the truth that there is probably no fixed determinant for entrepreneurship. Hong Kong and Singapore are both small, resource-poor city-economies and immigrant societies that began as British colonies in the nineteenth century owe much of their prosperity for the past 25 years to their role as regional entrepots. There is, however, a great difference in the political, social and economic evolution that gives rise to the contrasting role played by their entrepreneurs. This is because of the very different approaches adopted by their respective governments. The objective of this project is to understand the relevance of the different concepts and factors to Hong Kong entrepreneurs and at the same time, compare them with the Singaporean counterpart. At the same time, the distinctive characteristics of Hong Kong entrepreneurs are explored. Finally a comparison of the role of the government is made to help us understand the reasons why entrepreneurs play so different roles in the almost similar city-states.